The Potential Advantage of Targeting Both PD-L1/PD-L2/PD-1 and IL-10–IL-10R Pathways in Acute Myeloid Leukemia - Laura Jimbu (MDPI AG, 2021)
Tumor cells promote the suppression of host anti-tumor type 1 T cell responses by various mechanisms, including the upregulation of surface inhibitory molecules such as programmed death ligand (PD-L)-1, and the production of immunosuppressive cytokines such as interleukin-10 (IL-10). There are over 2000 trials investigating PD-L1 and/or its receptor programmed-death 1 (PD-1) blockade in cancer, leading to the approval of PD-1 or PD-L1 inhibitors in several types of solid cancers and in hematological malignancies. The available data suggest that the molecule PD-L1 on antigen-presenting cells suppresses type 1 T cell immune responses such as cytotoxicity, and that the cytokine IL-10, in addition to downregulating immune responses, increases the expression of inhibitory molecule PD-L1. We hypothesize that the manipulation of both the co-inhibitory network (with anti-PD-L1 blocking antibodies) and suppressor network (with anti-IL-10 blocking antibodies) is an attractive immunotherapeutic intervention for acute myeloid leukemia (AML) patients ineligible for standard treatment with chemotherapy and hematopoietic stem cell transplantation, and with less severe adverse reactions. The proposed combination of these two immunotherapies represents a new approach that can be readily translated into the clinic to improve the therapeutic efficacy of AML disease treatment.